Evaluation of Disparities in Emergency Department Admission and Wait Times for Non-English Preferred Patients - John Wong-Castillo; Daniel Berger; Juan Carlos Montoy; Riham Alwan (Western Journal of Emergency Medicine)
Introduction: Patients who prefer to communicate in a language other than English are vulnerable to the consequences of medical communication barriers. Studies of non-English language preferred (NELP) and English language preferred (ELP) patients have shown differences in rates of hospital admission and wait times—factors known to be related to increased costs and lower patient satisfaction. However, few studies include languages other than Spanish or account for patient acuity level. Methods: We performed a retrospective cohort study at an urban, Level I trauma center from January–December 2020. Patients were grouped by language preference, with NELP languages grouped into three categories: Spanish; Chinese (Mandarin, Cantonese, Taishanese, Taiwanese, and Zhongshan-Chinese dialect); and other (all other remaining languages). We extracted age, sex, race, ethnicity, language preference, emergency department (ED) discharge disposition, and Emergency Severity Index Score (ESI) from the electronic health record. The primary outcome was the hospital admission rate. Secondary outcomes were the time from patient arrival to placement in the treatment room and the time from patient arrival to disposition. We analyzed data with chi-square tests, logistic, and linear regressions. Results: Of the 58,079 unique ED encounters, 26.4% (15,307) patients identified as NELP. Within NELP patient encounters, 75.0% preferred Spanish, 13.9% preferred Chinese, and 11.1% preferred another language. After adjusting for age and acuity, Spanish language- and Chinese language-preferred patients were at 16% and 14% higher odds of admission, respectively (odds ratio [OR] 1.16, 95% confidence interval [CI] 1.10–1.23 and OR 1.14, CI 1.02–1.27 respectively), compared to ELP patients. NELP patients waited an average 5.4 minutes longer to be roomed (95% CI 4.46–6.29) and 15.6 minutes longer until disposition (95% CI 12.62–18.54, P<0.05). This discrepancy was greater for patients triaged at lower acuities, with ESI 5 Spanish language- and Chinese language-preferred patients waiting an average of 50.3 and 90.6 minutes longer than ELP patients until disposition (95% CI 17.67–83.57; and 95% CI 24.31–81.57 respectively). Conclusion: After adjusting for acuity level and age, non-English language preferred patients were at higher odds of admission and experienced disparate wait times, especially at lower acuity levels. Further investigation is needed to understand the causes of these differences and mitigate these health inequities.